Comparative efficacy of Escherichia coli lipopolysaccharide, oyster glycogen and enrofloxacin on uterine defense mechanism and fertility in crossbred cows with endometritis - PRASAD, J K; SAXENA, M S; PRASAD, SHIV; SINGH, G K (The Indian Journal of Animal Sciences, 2011)
Cows (48) tested positive for endometritis on the basis of appearance of cervical mucus and white side test were randomly divided into 4 groups with 12 cows in each group. In group A, 100 Î¼g of Escherichia coli LPS once, in group B, 500 mg OG once, in group C, enrofloxacin was infused intrauterine for 3 consecutive days and in group D, 20 ml PBS was infused once which served as control group. Endometrial biopsy was collected at 0 h and 72 h from all the cows for histopathological study. Uterine flushing was collected at estrus prior to infusion of drug (0 h) and at 24, 48 and 72 h post treatment for evaluation of changes in total protein concentration, TLC, PMNs%, and the total immunoglobulin concentration. The E. coli LPS and OG treatment significantly increased (P